Persepsi Masyarakat Terhadap Bantuan Pemerintah dan Perkembangan Koperasi Adat di Distrik Muara Tami Kota Jayapura - Deasy Rosmina Kresna Kaaf; Risky Novan Ngutra (Universitas Cenderawasih, 2025)
This study aims to analyze the effect of government assistance and business capability on financial performance, as well as the differences in capital, turnover, and profit before and after government assistance in the Indigenous Cooperative of Muara Tami District. The study employed a quantitative approach using multiple linear regression and paired sample t-test methods on 38 cooperative members. The results showed that simultaneously, government assistance and business capability have a significant effect on financial performance. Partially, government assistance has no significant effect, while business capability has a positive and highly significant effect. The paired sample t-test results indicated significant differences between before and after assistance for capital, turnover, and profit. This study concludes that business capability is the dominant factor in improving the financial performance of indigenous cooperatives. The recommendation for the government is not only to provide physical assistance but also to strengthen human resource capacity through intensive training and sustainable mentoring, as well as to improve the mentoring ratio to be more ideal. Keywords: government assistance, business capability, financial performance, indigenous cooperative